Persepsi Terhadap Diri dan Lingkungan Pada Remaja Penyalahguna Napza (Narkotika, Psikotrpoika dan Zat Adiktif) - Tina Afiatin (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2001)
The  purpose of this research is to know the perception to the characteristic of themselves and the  environment on adolescents abuser of narcotic, psy chotropic and addictive substance. The characteristic of themselves includes physical condition aspect,  psychological, social and  religious fife.  Whtie the environment mean the family,  the school and the  society around subjects.Carrying out  a depth interview and observation to  10 (ten) adolescents abuser of narcotic, psychotropic and addictive substance (7 males, 3 females) collected the  data. They ltved in Sleman. Yogyakarla territory.  Besides that also the information about the  subjects life were Inquired to 10 (ten) informants who knew about the  subjects life.The result of data  analysis qualitatively showed that  the  subjects perception to themselves generally (80%) felt not satisfied enough with  their physice/ condition. Psychologically. they had  lack of self-confidence, they felt inferior in the  social mteraction and  they felt less of religious life experience.  Their per ception to the fam/fy, they felt that they  were not quite accepted,  they  were  not quite understood and they often felt be neglected.  They were also not close with their father particularly.  Perception to the school environment, generally (70%) they felt were  accepted and popular although they realized also that their popularity in  negative  cases.  Most subjects (90%)  were  not  active and  in volved in the school activities.  Perception to the  society environments gener ally (80%) they felt they could be  accepted, even they felt closer compared with ,n  school  environment.  The  social activities in their area  more  empha sized physical  development aspects,  they had less of interest on  education aspect and  guiding of religious life.The  result of information from informants generally (90%) they stated thatmost subjects (80%) were spoiled by their parent with material. they got lack  of attention and  they  were usually egoists. They commonly was  easy to be per suaded by their friends  to follow negative deeds. such as  sitting idly on  the street and  disturbed other  people, drinking alcoholic drink and  drug abuse. Nevenheless, actually some  subjects  (8) also had  helpful character in the social activities. Kata Kuncl:   Persepsi, Remaja,  NAPZA